PSORIASIFORM DRUG ERUPTION INDUCED BY ANTI-TUBERCULOSIS MEDICATION: A CASE REPORT - SINDHU, NITIKA (International Journal of Current Pharmaceutical Research, 2023)
Objective: Psoriasiform drug eruptions can be induced by several drugs. Psoriasis is a chronic inflammatory disease characterized by T-cell-mediated cytokine production that drives the hyperproliferation and abnormal differentiation of keratinocytes. Drugs can cause new lesions when there is no prior history or family history of psoriasis. Based on the psoriatic drug eruption probability score, β‐blockers, synthetic anti‐malarial drugs, non‐steroidal anti‐inflammatory drugs (NSAIDs), lithium, digoxin and tetracycline antibiotics are relevant in psoriasis. Methods: A 58-year-old male was admitted to the Department of Respiratory Medicine at B. P. S G. M. C, Khanpur Kalan, Sonepat as a case of pulmonary tuberculosis and was put on anti-tubercular drugs CAT-I (according to RNTCP guidelines). The patient had a history of diabetes mellitus and hypertension for the past six years. On the third day of initiation of ATT, the patient started developing a psoriasiform rash. The psoriasiform rash began to improve within a few days after discontinuing the ATT. A causality assessment was done as per the WHO-UMC scale, which showed that the adverse events were likely caused due to the ATT. Results: Psoriasiform rash is a severe adverse drug reaction characterized by widespread lesions. Among all the various adverse drug reactions, lichenoid drug eruption is commonly associated with anti-tuberculosis medication and needs to be differentiated from psoriasiform eruption. The underlying pathomechanism of drug-induced psoriasiform eruptions remains uncertain, although several immunological interactions have been hypothesized. Conclusion: ATT has been reported to cause psoriasiform rash, and its drug component needs to be reconsidered in view of safer alternatives available.